Pengaruh Dukungan Sosial Orang Tua dan Keaktifan Berorganisasi Terhadap Penyelesaian Studi Mahasiswa (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the influence of parental social support and organizational involvement on the academic completion of students at the Faculty of Da’wah, IAI AL-AZIS. The focus of the study is to determine the extent to which these two variables, both partially and simultaneously, contribute to the timely graduation of students in the Islamic Communication and Broadcasting Program and Da’wah Management Program for the 2019–2024 cohorts. The research employs a quantitative approach using a survey method. A sample of 59 respondents was obtained through Slovin’s formula from the defined population. Data were collected via questionnaires and analyzed using multiple linear regression, Pearson and partial correlation tests, F-tests, and the coefficient of determination. The results indicate that, partially, parental social support does not have a significant effect on academic completion, whereas organizational involvement has a positive and significant impact. Partial correlation analysis further reveals that when organizational involvement is controlled, parental social support demonstrates a significant relationship with academic completion. Simultaneously, both variables together have a significant effect, with the model accounting for 16.1% of the variance. The findings underscore that organizational involvement plays a crucial role in students’ academic success, and when synergized with parental social support, both factors collectively contribute to achieving academic achievement.